The Pharmaceutical Availability of Gambier Leaves Bioactive Fraction Coated Tablet in Simulated Human Body Fluids - Sulistyowati, Indah; Yunarto, Nanang; Aini, Nurul; Arifin, Kelik M (Jurnal Kefarmasian Indonesia, 2018)
The widespread usage of traditional medicine either in the developed or developing countries, makes traditional medicine requirements become a major concern in terms of assuring the safety and effectiveness of treatment. WHO suggested dissolution study to support traditional medicine clinical trials. The catechins from Gambier could reduce atherosclerotic lesions case caused by elevated levels of cholesterol, LDL, and triglycerides. Catechin is hygroscopic that becoming unstable. Raising the stability, Gambier is made to a coated tablet. This study aimed to determine the condition of gambier leaves bioactive fraction coated tablet in simulated human body fluids through an in vitro testing using dissolution tester. Three formulations coated tablet with different coating percentage had been tested using dissolution tester apparatus. The test was conducted in water, acid, and buffer as dissolution medium to generate the dissolution profile. Tablet evaluation showed that the three formulations dissolved 71.25% ± 6.26 to 91.05% ±3.05 in the water, acid, and buffer dissolution medium. The gambier leaves bioactive fraction coated tablet had more than 70% pharmaceutical availability in simulated human body fluids.